Effects of Exchange Rate Fluctuations on the Balance of Payment in the Nigerian Economy - Felix Nwaolisa, Echekoba (International Journal of Scientific Research and Management (IJSRM), 2017)
This study seeks to find out how exchange rates fluctuation impacts on balance of payments (BOP).The secondary data where used specifically from CBN and National Statistics publications from 1990-2013. Average values for import, exports, exchange rate and balance of payment were collected for various years. Data were analyzed using multiple regression unit root test, making use of Augmented Dickey Fuller Test, E-view test statistics making use of variables, critical values and decision in carrying out unit root test. Where the findings showed that foreign exchange rate fluctuation in general affects some of these macro-economic variables.  The  Researcher concludes that government should harmonize monetary and fiscal policies to boost non-oil exports. A market driven exchange rate will encourage exports and take care of disequilibria in balance of payments.